PENINGKATAN KOMPETENSI GURU PAI DAN BUDI PEKERTI PADA SDLB MELALUI DIKLAT TEKNIS SUBSTANTIF GURU PAI DI LINGKUNGAN KANWIL KEMENTERIAN AGAMA PROPINSI JAWA BARAT - Muaripin Muaripin (Balai Diklat Keagamaan Bandung, 2018)
The purpose of this study was to determine the improvement of the competence of teachers of Islamic Religious Education at Special School Characteristics (PAI-BP SDLB) through the training of substantive technical education and training for Islamic Primary Education teachers in the regional office of the West Java provincial ministry of religion. Substantive technical training is the implementation of the teaching and learning process in order to improve the competence of PAI-BP SDLB teacher teachers as Civil Servants in the regional office of the West Java provincial Religion ministry. Professional teachers are competent teachers namely competence, pedagogic, personality, social and professional. The Bandung Diversity Education and Training Center has duties and responsibilities in terms of continuing professional development of teachers who are sustainable in the hope that the professionalism of PAI-BP SDLB Teachers will increase. The research method used is a quantitative method, the meaning is a research that is attempted to take or observe problems systematically and accurately regarding the facts and properties of certain objects. also uses survey methods, which is a method used to gather information in the form of opinions from a large number of people on certain topics or issues that aim to find out the general description of the characteristics of the population also trying to collect, describe and analyze data that are basically quantitative. From the results of research that has been done to improve the competency of PAI-BP SDLB Teachers experience improvement especially in understanding the deepening of the material and learning strategies to reach 80%, meaning that there are still 20% of training participants who still need to improve their competence. Key words: school is extraordinary, competent, professional.